PEMBUATAN DAN PENGEMBANGAN ALAT PENARIK KARET MOUNTING PADA SEPEDA MOTOR SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KOMPETENSI SISWA KELAS XI SMK MUHAMMADIYAH PETANAHAN - Rahmat Sumarno; Suyitno; Dwi Jatmoko; Slamet Riyadi; Tri Rofingi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to develop a motorcycle rubber mounting puller tool as a learning media to improve the competence of 11th-grade students at SMK Muhammadiyah Petanahan in the disassembly and assembly process of the motorcycle engineering department. This research uses the Research and Development (R&D) method with the 4-D (Four-D) development model from Thiagarajan, which consists of four stages: Define, Design, Develop, and Disseminate. The subjects of the trial were 10 students of class XI and one motorcycle engineering teacher at SMK Muhammadiyah Petanahan. The research instruments used were material expert validation sheets, media expert validation sheets, teacher response questionnaires, and student response questionnaires. Based on the results of the material expert validation and media expert validation, it shows that the motorcycle rubber mounting puller tool is very feasible with a percentage of 90%. The results of the student responses in the field trial obtained an average percentage of 93%. The teacher's response to the development of the rubber mounting puller tool obtained a percentage of 93.3%. With the percentage obtained, it is included in the very feasible category. In addition, from the trial results, it was also found that students stated that this tool is practical to use, supported by a simple design. This shows that the developed tool is feasible and can be used for the teaching and learning process in schools.